Применение вейвлет-анализа ля выделения информационных признаков акустических сигналов малых БПЛА - Беззабарный, Д. И. (ХНУРЕ, 2020)
The paper considers the possibility of using wavelet analysis to highlight information signs of acoustic signals of quadrocopters. The analysis of the wavelet spectrum obtained in the field experiment for the quadcopter DJI Phantom 3 is presented.
Keywords: БПЛА; акустический сигнал малых БПЛА